Food aid in Bangladesh: from relief to development - Atwood, David A.; Jahangir, A. S. M.; Smith, Herbie; Kabir, Golam (International Food Policy Research Institute, 2000)
This chapter examines food-aid trends and motivations and their impact in Bangladesh. As the world's second largest food-aid recipient (after Egypt) between 1975 and 1992, Bangladesh has operated a number of innovative and well-documented food-aid programs. Historically, donors have provided more than half of all the government's food supplies, often stipulating the distribution prices and offtake channels for their donations. Consequently, they have been key actors influencing the size, shape, and evolution of Bangladesh's public food distribution system (see Table 8.1).